Welfare mix e neoliberismo: un falso antagonismo - Dario Colombo (Quaderni di Sociologia, 2012)
The purpose of this paper is to clarify a way to legitimize the privatization processes concerning social protections. The category of Third Sector and those social theories that have contributed to enhance the varied nonprofit world are interpreted as both a medium and a relay of neoliberal proposals. Using an approach inspired by a foucauldian perspective – therefore being attentive to the intertwining between practices and games of truth –, the article examines how the rhetorics of solidarity and free choice concur to build a material alternative to public welfare. The two last sections present the Italian legal framework of Third sector agencies and an illustrative document about a reorganization of a local welfare system.